Effect of Abiotic and Biotic Elicitors on Callus and Suspension from Piper Betle L. Var. Nigra - Junairiah Junairiah; Lilis Sulistyorini; Nabilah Istighfari Zuraidassanaaz; Ni’matuzahroh Ni’matuzahroh (Syntax Idea)
Piper betle L. var. Nigra (black betel) contains secondary metabolites and has biological activity as antibacterial, antifungal, antioxidant, etc. To increase the production of secondary metabolites, an alternative method is needed, namely cell suspension culture. This study aims to determine the effect of abiotic and biotic elicitor on callus biomass produced from cell suspension culture. Leaf explants were grown on Murasige and Skoog (MS) medium with the addition of growth regulator 2.4-D 0.5 mg/L and BAP 2.0 mg/L with abiotic elicitors CuSO4, ZnSO4, HgCl2 and CoCl2 with a concentration of 0.5; 1.0 and 2.5 mg/L. The biotic elicitor used was Aspergillus niger with a concentration of 0.025%; 0.050% and 0.1%. The cultures were incubated for 8 weeks. 0.5 g callus was subcultured on 25 mL cell suspension medium. The suspension culture was shaken at 110 rpm. In this suspension culture, the callus was incubated for 3 weeks. After 3 weeks of age callus on suspension medium was harvested and weighed the fresh and dry weight. The results showed that the highest average dry weight was found in the treatment with abiotic elicitor CuSO4 0.5 mg/L at 0.088 g.